KONSEP PEMBELAJARAN ( BACK TO AL-QURâAN) - Fatonah, Isti (JURNAL TARBAWIYAH, 2014)
Indonesian education is essentially form a complete human beings who believe, knowledgeable and charity. To achieve these objectives, in general, the Quran can be used as guidance. Lifelong education motto of life long education and education for all and all for education should be a principle of life. Learning is part of worship. Quran clues that describe methods of education and learning that can touch the mind and soul of learners. Lifelong education motto of life long education and education for all and all for education should be a principle of life. Keywords: Learning is a part of worshipKonsep Pembelajaran dalam Al-Qurâan